Entrepreneurship Training Model Based on Sad Kerthi Loka Bali Perspective - Muku, I Dewa Made Krishna; Sudiarta, I Gusti Putu; Nitiasih, Putu Kerti; Warpala, I Wayan Sukra (Journal of Ecohumanism, 2025)
The management of Village-Owned Enterprises (BUMDes) in Bali faces the problem of limited business variety and low entrepreneurial competence of managers, leading to less than optimal utilization of local potential. The training that has been applied so far still focuses on administration and financial reporting, without developing innovation and creativity skills based on local wisdom. As a solution, an entrepreneurship training model was developed that integrates the EntreComp global competency framework with the local values of Sad Kerthi Loka Bali. The Research and Development (R&D) method with the ADDIE model was used in this research, which includes analysis, design, development, implementation, and evaluation. Model validation by experts showed an excellent level of feasibility, while the training trial resulted in an increase in participants' competency scores from an average of 44.4 in the pre-test to 83.1 in the post-test. On average, there was an increase of 38.7 points converted into a gain value of 0.656 which is included in the moderate category. This confirms the effectiveness of the model. In addition to enhancing creativity and innovation skills, the training instills spiritual and social values that are aligned with Balinese culture, encouraging a balance between economic, social and environmental aspects. The practical implications of the model can serve as a guide for BUMDes managers and policy makers in developing sustainable businesses. The model also has the potential to be adapted in other regions with similar local wisdom.